Analisis Strategi Inovasi Bisnis Berbasis Digital dalam Membangun Keunggulan Bersaing (Competitive Advantage) UMKM Fashion Aksesoris di Desa Rasabou Kecamatan Hu’u - Muhammad Nur Rizal; Mulyati Mulyati; Rizky Ramadhan (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Advances in digital technology are driving MSMEs to innovate in order to enhance their competitiveness. This descriptive qualitative study aims to analyze the implementation of digital-based business innovation strategies in building competitive advantage among fashion accessories MSMEs in Rasabou Village, Hu'u Subdistrict, Dompu Regency. Data were collected through observation, interviews, and documentation with purposively selected informants, then analyzed using the Miles, Huberman, and Saldaña model. The results show that digital innovation is implemented through the use of Facebook and WhatsApp for promotion, communication, and the dissemination of product information. These efforts have successfully increased product visibility, expanded market reach, and built customer trust and loyalty. The competitive advantages of MSMEs are reflected in product uniqueness, competitive pricing, adaptation to trends, and a positive image. However, the use of technology remains limited to promotion and has not yet been integrated into all aspects of business management. More comprehensive development of digital innovation is needed to achieve operational efficiency and sustainable competitive advantage.